2010
DOI: 10.1002/cne.22429
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of cannabinoid signaling in mouse retina

Abstract: Cannabinoid receptors and their ligands constitute an endogenous signaling system that is found throughout the body, including the eye. This system can be activated by Δ 9 -tetrahydrocannabinol, a major drug of abuse. Cannabinoids offer considerable therapeutic potential in modulating ocular immune and inflammatory responses and in regulating intraocular pressure. The location of cannabinoid receptors 1 (CB 1 ) in the retina is known, but recently a constellation of proteins has been identified that produce an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
48
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 99 publications
(151 reference statements)
7
48
1
Order By: Relevance
“…Cnrip1 expression is observed in the outer plexiform layer (OPL) of the mouse retina 36 and morpholino loss of function studies have suggested that Xenopus laevis cnrip1 regulates eye development 35 . However, we detected no eye defects in our maternal/zygotic cnrip1a;cnrip1b double mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Cnrip1 expression is observed in the outer plexiform layer (OPL) of the mouse retina 36 and morpholino loss of function studies have suggested that Xenopus laevis cnrip1 regulates eye development 35 . However, we detected no eye defects in our maternal/zygotic cnrip1a;cnrip1b double mutants.…”
Section: Discussionmentioning
confidence: 99%
“…CRIP1a was initially characterized for its ability to bind to a segment of the distal C-terminal of the CB 1 R [1]. Following that report, studies of retinal circuitry showed that CRIP1a could be found in amacrine cells, and in certain cone (but not rod) terminals [33]. The CB 1 R-CRIP1a presynaptic co-localization was juxtaposed across from postsynaptic diacylglycerol lipase at photoreceptor/Type1 OFF cone-bipolar cell synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Although CRIP1a is conserved among mammals and fish, the presence of CRIP1b is limited to primates [11]. CRIP1 proteins have been has been identified immunologically in neurons in the superior cervical ganglion [11], striatum [17], glutamatergic CA3 pyramidal neurons in the hippocampus [18, 19] and retina [20]. …”
Section: Introductionmentioning
confidence: 99%